Mass Shootings and Their Proximity to a Public or Private School: Protecting the Health and Livelihood of Our Children. Issue 11 (November 2022) - Sen-Crowe, Brendon; Autrey, Cody; Newsome, Kevin; Mckenney, Mark; Elkbuli, Adel
Introduction: Firearm-related violence occupies the third leading age-adjusted mortality rate among all mechanisms of injury. We aim to analyze the distribution of mass shootings in relation to the distance to the nearest public/private school in the United States. Methods: A retrospective study investigating mass shootings and proximity to school areas. Information regarding mass shootings was obtained from the Gun Violence Archive. The locations of public/private schools for the 2019-2020 school year were obtained from the National Center for Education Statistics and the Euclidian distance from a mass shooting to the nearest school was measured. Results: There were 417 mass shootings in 2019 and 610 in 2020. The average distance from a mass shooting to the nearest public/private school was 0.52 miles in 2019 and 0.57 miles in 2020. Most mass shootings occurred within 0.30 miles of a school in 2019 and 0.40 miles in 2020. There was no significant association between average distance of a mass shooting to a public/private school and the population density in 2019 ( P = .313) or 2020 ( P = .351). Conclusion: The growing number of mass shootings from 2019-2020 was associated with an average distance of <0.60 miles from the location of a mass shooting to a public or private school, highlighting the danger posed to children living and learning in these areas. Mass shootings are prevalent throughout the country and the close proximity of these events to places of learning warrants further investigation into policies and preventive measures aimed at preventing gun violence occurring near schools.